A new species of Tetragonopterus (Characiformes: Characidae) from central Amazon Lowlands, Brazil - Urbanski, Bruna Q. [UNESP]; Melo, Bruno F. [UNESP]; Silva, Gabriel S. C. [UNESP]; Benine, Ricardo C. [UNESP] (FapUNIFESP (SciELO), 2018)
A new species of Tetragonopterus is described from lowland rivers of Central Amazon. It differs from congeners by having a vertically-oriented patch of dark pigmentation limited to posterior portion of the caudal peduncle and by bearing five thin and sharp teeth on dentary, along with other morphometric and meristic features. We hypothesize that the new taxon belongs to the herein named “Tetragonopterus anostomus clade” that includes T. anostomus, T. denticulatus, T. kuluene, and T. juruena.
Keywords: Biodiversity; Freshwater fishes; South America; Taxonomy; Tetragonopterinae